The representation of death in the African novel in French - (:unkn) unknown (My University, 2004)
In the African novel written in French, death prervades the narrative fabric. What strikes the reader is the omnipresence of death, as feature in the titles. The recurrence of the motif of violent death is to be set in relation with authoritarian regimes in Africa. The evolution of African society has introduced a significant factor underlying the novel, which is the deritualisation of death as a consequence of the devitalisation of myths. Facing existential angst, the novel reappropriates the way of thinking about death extant among traditional African societies. It consists in bringing into play the permanent conflict between " impulsie imagination " and " rational imagination " one the one hand, and their complementarity on the other. The dynamic antagonism opposing rationality and impuse in the constructive phase of their duality enables the creation of myths which make life tolerable. Against this cultural background the novel builds utopias to postulate another dimension to the future.
Keywords: African Research